49th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2013
DOI: 10.2514/6.2013-3780
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of OH* Radiation as a Marker for the Heat Release Rate in High-Pressure Hydrogen Liquid Rocket Combustion

Abstract: The identification of the volumetric heat release rate is of great importance in combustion research, e.g. for the investigation of combustion instabilities in liquid rocket motors. Since it is not feasible to measure this quantity directly with reasonable effort, the heat release is often assumed to be directly proportional to the radiation of the excited hydroxyl radical (OH * ). This paper investigates whether this assumption can be used for diagnostics of the turbulent combustion in liquid rocket motors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Usually, the measurement of ' q ′ (t) is approximated using the §ame radiation which is easy to measure. In hydrogen/oxygen combustion, the radiation of OH* [25] has been used as a marker for ' q ′ (t) due to its good detectability [31,32]. This is also the approach chosen for the presented work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the measurement of ' q ′ (t) is approximated using the §ame radiation which is easy to measure. In hydrogen/oxygen combustion, the radiation of OH* [25] has been used as a marker for ' q ′ (t) due to its good detectability [31,32]. This is also the approach chosen for the presented work.…”
Section: Methodsmentioning
confidence: 99%
“…This is also the approach chosen for the presented work. As discussed in detail in other work by the authors [33], the selected measurement setup allows the measured OH* radiation intensity signals to be interpreted as an approximation for the oscillation of ' q ′ [32]. For the described analysis method, only the frequency and phase information of the ' q ′ (t) signal and not the amplitudes are required.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies that observed OH* chemiluminescence in turbulent flames and flames with high strain rates reported poor agreement with heat release in that the emission varies strongly with turbulence levels and even disappears at high strain rates 14;20-22 . At elevated pressures, it has been shown computationally that thermal excitation of OH molecules is the primary source for OH* radicals rather than chemical excitation that would be associated with the heat generating reaction path 23 .…”
Section: B Use Of Chemiluminescence As An Optical Diagnosticmentioning
confidence: 99%
“…Areas of high combustion rate and density gradients can be detected by OH* emission and visible imaging, respectively. Recent work has highlighted the limitations of OH* imaging in high-pressure oxygenhydrogen combustion [11]. There are rising doubts as to its often assumed analogy with local heat release rate.…”
Section: Introductionmentioning
confidence: 99%